(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In this study, we examine the gendered lens through the lens of some of society’s most recentshifts. The purpose is to analyze how gender roles, identities, and disparities have changed through timeand to discuss the difficulties and obstacles that have arisen as a result. This research delves at howgender intersects with other social categories including ethnicity, socioeconomic status, and sexualorientation to produce unique personal and societal outcomes. In the first part of the research, we look athow conventional gender roles have affected society norms and expectations by tracing the evolution ofgender and its social construction. It then looks at how gender roles have changed over the last severaldecades, analyzing trends in employment equality, political representation, educational opportunities,and family arrangements, among others. An growing variety of gender identities and expressions,including those of trans and non-binary people, are being acknowledged with particular emphasis.